A utilização da logística reversa como fonte sustentável e econômica para as empresas localizadas na zona franca de Manaus - Silva, Carolina Postigo (2023)
The objective of the research was to analyze the Free Trade Zone of Manaus in view of the need for conservation of the Amazon through sustainable alternative measures in the exercise of business activities in this region. The constitutional norms that deal with the Free Trade Zone of Manaus were analyzed, as well as its importance for the maintenance of the standing forest, presenting the attacks and discussions around the model, the tax incentives granted to companies, the relevance and challenges of the Polo Manaus Industrial. Next, the concepts and norms related to the balance between sustainable development and economic development were demonstrated, which is intrinsic to the application of the intergenerational principle, aiming at development without depleting the source of resources. The problem of solid waste was investigated and presented as a measure for waste management, the implementation of reverse logistics, which immediately, the investment will contribute to the conservation of the environment and in the long term, will serve as a source of economic income . Based on the fundamentals explored, the case study demonstrated that reverse logistics is one of the measures capable of minimizing the environmental impact, generating a sustainable source of income, fostering the strengthening of the corporate image and environmental awareness for companies located in the ZFM. With regard to the methodology employed, it is based on the descriptive exploratory study, using the deductive scientific method of approach; as for the means, the research was bibliographical and documental through on-site research in the investigated company with the making of a photographic report and collection of information and as for the purposes, qualitative. In this way, the research concludes for the continuity of the defense of the Manaus Free Trade Zone model, despite the need to reflect on its limitations and threats, as well as the need to safeguard the Amazon from environmental impacts and damages resulting from the inadequate disposal of solid waste. Therefore, reverse logistics was classified as one of the sustainable alternatives to solve the solid waste problem of companies in the Manaus Free Trade Zone, which should take into account each segment of business activity. However, it was revealed that isolated measures by the private sector are not enough, it is also necessary for the Public Power to rigorously supervise compliance with the legislation that deals with solid waste management and reverse logistics, starting to develop educational campaigns. And in the end, it was recommended to expand studies aimed at other segments of the Manaus Free Trade Zone, as a way of revealing new alternatives for sustainable income generation by companies in the Manaus Free Trade Zone.